Therapy for Persistent Clinically Significant Gastro-oesophageal Reflux: The Design of a Randomized Clinical Trial of Surgical versus Medical Management - Whelan, Gregory (My University, 1979)
Every day a physician treating patients carries out a series of experiments - whether he is aware of it or not. Many of the decisions he makes need to be made against a background of inadequate information concerning the effectiveness of the therapies he prescribes.
This manuscript begins with a review of the currently available scientific literature concerning gastro-oesophageal reflux - its pathogenesis, diagnosis and therapy. Then, the design of a prospective randomized control trial of therapy for persistent clinically significant gastro-oesophageal reflux is described. The design is for an intervention study to determine the effectiveness of therapy in patients randomized to either surgical or medical treatment for this disorder.
Subjects for the study will be drawn from among patients referred from primary care physicians to gastroenterology clinics for treatment. These patients to be eligible will have to have failed to respond to standard medical therapy.
Data for analysis will be collected utilizing a self administered questionnaire to record symptoms and the degree of incapacity caused by them.
It is hoped that results obtained from the performance of the trial described in this document will be of assistance in guiding the decision making process of physicians caring for patients with symptomatic gastro-oesophageal reflux.
Keywords: Medical Sciences; Medical Sciences